Química verde no ensino superior de química: estudo de caso sobre as práticas vigentes em uma IES paulista - Saqueto, Karla Carolina (2015)
The main objective in this paper is to analyze the scenario in Green Chemistry (GC) education practiced in a São Paulo-based IES (Higher Education Institute). This was achieved by studying the proposals which are especially directed to the development, adaptation and application of didactic experiments which have inserted GC contents. This scope was achieved by implementing a qualitative approach-based research methodology through document analysis, questionnaires and semi-structured interviews, based on the methodological assumptions of content analysis alongside an extensive literature review that contributed to the GCE (Green Chemistry Education) publications. The study consisted of five experimental subjects in different areas of chemistry, which were observed and followed with regards to inserting GCE by introducing GC experiments and/or guidelines. Based on the data attained, this paper proposes six principles of GCE, which together with the Green Star (GS) holistic metric allow a better analysis and range of the experimental practices considered green. Among the GCE principles, the introduction of questioning/contextualization (STS approach) and research incentive proved to be vitally important. As observed through the introduction of the green experiments Detection of Metals routinely identified and Extraction and quantification of Fe (III) ions in soil samples , besides learning conceptual and procedural contents, some practices promoted attitudinal contents, which play an important role related to stimulating critical thinking, integrated approach to the exercise of citizenship and responsibilities for future competent professional practices and committed to humanistic, ethical criteria, and scientific rigor.